Bioactive Compounds of Polygonatum sibiricum - Therapeutic Effect and Biological Activity - Zhao, Xin; Patil, Suryaji; Qian, Airong; Zhao, Caihong (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Abstract: Plants serve as an important source of medicinal compounds, and their use in various diseases dates back hundreds of years. One such plant-based compound and the discovery of the antimalarial drug, artemisinin, has significantly brought phytomedicines into the spotlight and has enhanced the understanding and, consequently, the application of formulations derived from plants. Traditional Chinese Medicine (TCM), which is based primarily on plants, holds immense potential and is an unexplored source for modern medicine. Many herbs, including Polygonatum sibiricum (PS), are used in Chinese medicine to treat various diseases. Polygonatum sibiricum (PS) belongs to the Liliaceae family and is used not only as a medicinal but also dietary supplement. PS has a highly diverse composition of bioactive compounds such as flavones, homoisoflavanone, alkaloids, lignins, steroid saponins, triterpenoid saponins, polysaccharides, etc. Because of such diverse composition, PS has been used as an anti-aging, anti-inflammatory, anti-osteoporotic agent, as well as an immunity booster, sleep enhancer, etc. Therefore, in this article, we review the therapeutic effect of bioactive compounds such as polysaccharides, saponins, and PS extract in various diseases and their biological activities in fatigue, immunity, sleep, anti-aging, etc.
Keywords: Phytomedicines